Radiological Diagnosis vs. Surgical Results for Acute Appendicitis in 450 Patients at Qazi Hussain Ahmad Hospital, Nowshera - Erum Habib, Kamran Ahmad, Zarlakhta Zahir, Rashda Khattak, Humera Habib, Jehan Ara, (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: Investigating the surgical findings of acute appendicitis against the radiological diagnosis Methods: This crosssectional study was conducted in the department of Radiology Qazi Hussain Ahmad hospital Nowshera from Jan 2019 to Dec 2019. For sample size who sample size calculator was used. Patients who reported right iliac fossa discomfort, a symptom often associated with acute appendicitis, were included in the research. Participants had to be between the ages of 12 and 65, have had abdominal discomfort, and have it focused in the right iliac fossa/ lower quadrant. Patients were sent to an experienced radiologist for Ultrasonography when they were thought to be experiencing symptoms of acute appendicitis. Patients with negligible ultrasonographic results were assessed for right lower abdominal discomfort. Those with ultra-sonographic results highly indicative of acute appendicitis were subsequently evaluated to rule out complications. Results: There were 450 participants included in our analysis, ranging in age from 6 to 55 (mean 337.8 years), and with a male to female ratio of 3.19:2. We performed 550 ultrasonographic scans on these patients and 500 regular urine examinations. Only 350 patients with suspected acute appendicitis confirmed their suspicions by imaging tests, whereas 450 patients with a confirmed clinical diagnosis had surgery. One hundred forty-four individuals had a laparoscopic appendectomy, and 300 patients underwent open surgery. Each patient had a tissue sample taken for histopathology. Sonographic findings included the presence of an appendix in 351 patients (79 percent), an uncompressible tubular structure in 351 patients (79 percent), fluid in the right iliac region in 118 (13.11%), 103 (11.44%) patients have mesenteric node enlargement, 23 (2.55%) have high-up subhepatic appendix and 24 (2.66%) have mass formation in Hyperemic swelling of the appendix occurred in 648 (72%), blackened/gangrenous appendix in 84 (9.33%), pus around the appendix in 57 (6.33%), enlarged mesenteric lymph nodes in the appendix in 210 (23.33%), perforated appendix in 58 (6.44%), early mass formation in 35 (3.88%), and subhepatic appendix in 23 (2.55%) patients. Practical implication: The results of this study will help the surgeon to make Clinical judgments of acute appendicitis. Conclusion: It is recommended to diagnose appendicitis using Ultrasonography since it is a non-invasive examination. An appropriate diagnostic approach for evaluating appendicitis complications with high sensitivity. Acute appendicitis can be accurately diagnosed 84% of the time using Ultrasonography, although there is a 15% false negative rate. Keywords: Incompressible appendicitis, tubular structure, clinical diagnosis, radiological diagnosis